Research on Lithium Battery Recycling and Utilization - Yan, Zhenyu (International Journal of Materials Science and Technology Studies, 2024)
With the rapid development of new energy, lithium batteries, as one of the key technologies in the field of energy storage, play an important role. However, with the widespread application of lithium batteries, the problem of their disposal has become increasingly prominent, which not only affects the environment but also wastes precious resources. This article analyzes the domestic new energy lithium battery market situation and finds that domestic new energy is developing rapidly and the lithium battery market has huge potential. In terms of lithium battery recycling and utilization, comparison shows that foreign lithium battery recycling technology is relatively mature, but there are certain challenges in adapting to domestic actual conditions and cost control. Although there are some advanced recycling technologies in China, the overall level still needs to be improved.